THE IMPACT OF SMART TECHNOLOGY ON PRIMARY SCHOOL LEARNERS: A CASE STUDY - Jame, Mst. Sajedha Akter; Hossain, S M Saadat; Rahman, Mohammad Mustafizur (JTechLP: Journal of Technology in Language Pedagogy, 2026)
This case study closely examines the detrimental impacts of smart technology on primary school learners in Bangladesh and aims to deeply understand of the multi-layered challenges posed by the widespread use of digital devices. Applying a mixed-method approach, both qualitative and quantitative data were collected from 40 guardians of learners from 04 primary schools in Bogura, Bangladesh. The Findings reveal that most of primary learners are exposed to modern technologies, with a significant percentage engaging with gaming apps and video-sharing platforms. Participants expressed serious concerns about the adverse consequences of technology usage on children’s learning and behavior. Moreover, a majority of the participants highlight the appropriateness of introducing smart technologies to children, the risk of addiction, and the potential impact on children's ability to distinguish right from wrong. The study emphasizes a balanced and carefully monitored integration of technology in primary education, considering different perspectives and potential risks. It suggests that educators, parents, and policymakers should adopt appropriate strategies that can encourage appropriate use of digital tools to ensure healthy learning environments rather than hinder young learners’ educational and social development.